PENGGUNAAN GAYA BAHASA SINDIRAN SINISME DAN SARKASME DALAM LINGKUNGAN PASAR KARUWISI KOTA MAKASSAR - Sri Asrianti Abidin; Sakaria Sakaria (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2022)
The Use of Cynicism and Sarcasm Satire Language Styles in the Karuwisi Market Environment Makassar City. This study aims to describe the use and function of sarcasm and sarcasm in the Karuwisi market environment of Makassar City. This type of research is descriptive qualitative research. The focus of this research is sentences containing satire, cynicism and sarcasm in the Karuwisi market environment Makassar City. Data collection techniques were carried out by listening, recording, and note-taking techniques. The results of the study revealed that several forms of sarcasm and sarcasm were found in the Karuwisi market environment Makassar City. The satire of cynicism is divided into comparative forms, rhetorical question sentences and contradictions, while the style of sarcasm satire is divided into forms of swearing, accusations, criticism, and insults. Then the function of using cynical and sarcasm satire language style includes the function of convincing the listener, the function of condescending, the function of affirmation, the function of reprimand, and the function of conveying opinions.